2004
DOI: 10.4049/jimmunol.173.1.566
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine Receptor-Mediated Recognition of Archaeosome Adjuvant Promotes Endocytosis and MHC Class I Cross-Presentation of the Entrapped Antigen by Phagosome-to-Cytosol Transport and Classical Processing

Abstract: Archaeal isopranoid glycerolipid vesicles (archaeosomes) serve as strong adjuvants for cell-mediated responses to entrapped Ag. We analyzed the processing pathway of OVA entrapped in archaeosomes composed of Methanobrevibacter smithii lipids, high in archaetidylserine (OVA-archaeosomes). In vitro, OVA-archaeosomes stimulated spleen cells from OVA-TCR-transgenic mice, D011.10 (CD4+ cells expressing OVA323–339 TCR) or OT1 (>90% CD8+ OVA257–264 cells), indicating both MHC class I and II presentations. In v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 57 publications
0
55
0
Order By: Relevance
“…However, vaccinating against a single antigen has disadvantages, as it is unknown which of the identified antigens have the potential to induce an effective antitumor immune response [22]. Tumor lysates contain multiple known as well as unknown antigens that can be presented to T cells by MHC class I and class II pathways [23]. Therefore, lysateloaded DCs are more likely to induce a polyclonal expansion of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, vaccinating against a single antigen has disadvantages, as it is unknown which of the identified antigens have the potential to induce an effective antitumor immune response [22]. Tumor lysates contain multiple known as well as unknown antigens that can be presented to T cells by MHC class I and class II pathways [23]. Therefore, lysateloaded DCs are more likely to induce a polyclonal expansion of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Such errors include a proteasome degradation by mistake, failure to be transported by TAP, and a small number of specific T cell receptors to identify them (Rivett and Hearn, 2004;Gurnani et al, 2004). Therefore, even though the HBx1, HBx3, and HBx4 epitopes showed ideal T2 cells binding or T cell stimulation, the lower immunity responses they induced in our experiments reveal that they are not CTL epitopes with the appropriate immunogenicity.…”
Section: Discussionmentioning
confidence: 53%
“…VP1-OVA 252-270 and VP1-OVA 320-343 ). The fact that the complete OVA protein failed to stimulate OT1 and only marginally OT2 cells could be attributed to the low antigen processing efficiency of soluble OVA by APCs in vitro and in vivo [12,21]. Interestingly, we found that OT1 and OT2 cells stimulated with high amounts of PLP also showed a low level of proliferation.…”
Section: Discussionmentioning
confidence: 60%